"Just a virus" or politicized virus? Global media reporting of China on COVID-19. Issue 1 (1st January 2023) - Fan, Xinguang; Zhang, Yongjun
Abstract: This study examines how China was covered and framed in global media reporting during the early stage of the coronavirus pandemic. Relying on a global multilingual COVID-19 online news narratives dataset, we propose multidimensional indicators to assess cross-country and cross-period variations in media discourses on China throughout the year of 2020. We derive and assess two hypotheses to explore factors accounting for the variations. The ideology-conflict hypothesis argues that the ideology distance from China determines the media attention and framing toward China in terms of COVID-19 reporting, while the crisis-mitigation hypothesis emphasizes that the domestic pandemic situation is associated with media discourses on China. Empirical analysis based on data compiled from various sources finds no evidence for the ideology-conflict hypothesis and moderate support for the crisis-mitigation hypothesis. Changes in the coronavirus situation and policy reactions are associated with changes in media coverage of China and the use of politicized terms over time. We conclude by discussing the implications of using online media data to understand the COVID-19 infodemic and its contribution to the emerging field of computational sociology.